An Unsettled Promise: The Newborn Piglet Model of Neonatal Acute Respiratory Distress Syndrome (NARDS). Physiologic Data and Systematic Review - Spengler, Dietmar; Rintz, Nele; Krause, Martin F. (Frontiers in Physiology, 2019)
Despite great advances in mechanical ventilation and surfactant administration for the newborn infant with life-threatening respiratory failure no specific therapies are currently established to tackle major pro-inflammatory pathways. The susceptibility of the newborn infant with neonatal acute respiratory distress syndrome (NARDS) to exogenous surfactant is linked with a suppression of most of the immunologic responses by the innate immune system, however, additional corticosteroids applied in any severe pediatric lung disease with inflammatory background do not reduce morbidity or mortality and may even cause harm. Thus, the neonatal piglet model of acute lung injury serves as an excellent model to study respiratory failure and is the preferred animal model for reasons of availability, body size, similarities of porcine and human lung, robustness, and costs. In addition, similarities to the human toll-like receptor 4, the existence of intraalveolar macrophages, the sensitivity to lipopolysaccharide, and the production of nitric oxide make the piglet indispensable in anti-inflammatory research. Here we present the physiologic and immunologic data of newborn piglets from three trials involving acute lung injury secondary to repeated airway lavage (and others), mechanical ventilation, and a specific anti-inflammatory intervention via the intratracheal route using surfactant as a carrier substance. The physiologic data from many organ systems of the newborn piglet - but with preference on the lung - are presented here differentiating between baseline data from the uninjured piglet, the impact of acute lung injury on various parameters (24 h), and the follow up data after 72 hours of mechanical ventilation. Data from the control group and the intervention groups are listed separately or combined. A systematic review of the newborn piglet meconium aspiration model and the repeated airway lavage model is finally presented. While many studies assessed lung injury scores, leukocyte infiltration, and protein/cytokine concentrations in bronchoalveolar fluid, a systematic approach to tackle major upstream pro-inflammatory pathways of the innate immune system is still in the fledgling stages. For the sake of newborn infants with life-threatening NARDS the newborn piglet model still is an unsettled promise offering many options to conquer neonatal physiology/immunology and to establish potent treatment modalities.